Checking for Open Bisimilarity in the pi-Calculus - Frendrup, Ulrik; Jensen, Jesper Nyholm (BRICS Report Series, 2001)
This paper deals with algorithmic checking of open bisimilarity in the pi-calculus. Most bisimulation checking algorithms are based on the partition refinement approach. Unfortunately the definition of open bisimulation does not permit us to use a partition refinement approach for open bisimulation checking directly, but in the paper 'A Partition Refinement Algorithm for the pi-Calculus' Marco Pistore and Davide Sangiorgi present an iterative method that makes it possible to check for open bisimilarity using partition refinement. We have implemented the algorithm presented by Marco Pistore and Davide Sangiorgi. Furthermore, we have optimized this algorithm and implemented this optimized algorithm. The time-complexity of this algorithm is the same as the time-complexity for the first algorithm, but performance tests have shown that in many cases the running time of the optimized algorithm is shorter than the running time of the first algorithm. Our implementation of the optimized open bisimulation checker algorithm and a user interface have been integrated in a system called the OBC Workbench.The source code and a manual for it is available from http://www.cs.auc.dk/research/FS/ny/PR-pi/.